Penggunaan metode collection-centered dalam kegiatan evaluasi koleksi di Perpustakaan Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon - Yunus Winoto; Dewi Kusumawati (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
Research on collection evaluation based on collection-centered methods aims to increase selector knowledge about collection and use so that it can measure success in developing and managing collections effectively. The location of the study was conducted at the IAIN Syekh Nurjati Library Center in Cirebon. The method used is a qualitative research method with a case study approach. Data obtained through observation, in-depth and unstructured interviews supported by triangulation by college librarians. Based on the results of the study it can be concluded that the results of the evaluation of the list checking process carried out by the IAIN Syekh Nurjati Cirebon Library Center has been well marked by the process of mapping the strength of collections, using the checklist form, overcoming the existing collection gap to determine collection priorities based on checking by librarians. In planning collection procurement, librarians always involve the opinions of some lecturers as experts ( expert opinion) in determining relevant and up-to-date collections according to the curriculum in IAIN Syekh Nurjati Cirebon. Collection at the IAIN Syekh Nurjati Cirebon Library Center has fulfilled three indicators of collection standards and continues to make efforts to perfect the collection in accordance with applicable standards.